(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
The most common type of biliary system cancer is gallbladder cancer. The fifth most common type of gastrointestinal tract cancer. In 2022, 1.2% of Indians had GBC (Globocan). Gallbladder cancer was more common in women and Caucasians than in African Americans and men. (three to four times)[1].